A new encrypted method in image steganography - Sabyasachi Pramanik; R P Singh; Ramkrishna Ghosh (Institute of Advanced Engineering and Science, 2019)
Steganography is data hiding technique in internet. Here we send CAPTCHA codes within a cover image using Image steganography. CAPTCHA are the crazy codes. They are used in human response test. The word is actually an acronym for: